Pemanfaatan Asap Detektor untuk Pembuatan Smart Garasi Berbasis IoT - Hartono, Jamrud Ivan; Rahayuda, I Gede Surya (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2025)
As a response to increasing safety and efficiency problems, utilizing the Package Tracer simulation, this research aims to create a smart garage that provides a new solution to the public to provide warnings to avoid fires, vehicles are not left in closed garages for too long so that things don't happen. dangerous things and to increase garage efficiency. This research uses experimental and quantitative methods, which are the methods used to design a system. With this system, garages will avoid theft and fires to quickly apply sensor advances in various situations, with a focus on vehicles that stay too long in the garage and smartphone-enabled garages, which is an important problem in many homes. Utilizes Packet Tracer simulation, emphasizing factors such as placement, sensitivity settings, and effective use. This article provides valuable insight into potential opportunities for future research and innovation in the field of smoke detection. This research highlights the importance of proper use and maintenance in maximizing the capabilities of smoke detectors.